2019
DOI: 10.3390/s19153312
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Motion Artifacts in Photoplethysmograph Sensors during Intensive Exercise for Accurate Heart Rate Calculation Based on Frequency Estimation and Notch Filtering

Abstract: With photoplethysmograph (PPG) sensors showing increasing potential in wearable health monitoring, the challenging problem of motion artifact (MA) removal during intensive exercise has become a popular research topic. In this study, a novel method that combines heart rate frequency (HRF) estimation and notch filtering is proposed. The proposed method applies a cascaded adaptive noise cancellation (ANC) based on the least mean squares (LMS)-Newton algorithm for preliminary motion artifacts reduction, and furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…The ECG signal was used to derive the reference HR using a standard peak detection method based on the Pan-Tompkins algorithm [17]. 2) Adaptive Filter for Motion Artifact Removal: Adaptive filters are commonly used to remove motion artifacts from PPG signals [10], [18]- [22]. Often, adaptive noise cancellation (ANC) is performed using each accelerometer axis in sequence [10], [20], [21].…”
Section: A Databasesmentioning
confidence: 99%
See 3 more Smart Citations
“…The ECG signal was used to derive the reference HR using a standard peak detection method based on the Pan-Tompkins algorithm [17]. 2) Adaptive Filter for Motion Artifact Removal: Adaptive filters are commonly used to remove motion artifacts from PPG signals [10], [18]- [22]. Often, adaptive noise cancellation (ANC) is performed using each accelerometer axis in sequence [10], [20], [21].…”
Section: A Databasesmentioning
confidence: 99%
“…2) Adaptive Filter for Motion Artifact Removal: Adaptive filters are commonly used to remove motion artifacts from PPG signals [10], [18]- [22]. Often, adaptive noise cancellation (ANC) is performed using each accelerometer axis in sequence [10], [20], [21]. However, applying the adaptive filter with all three signals at once allows the filter weights to be properly adjusted with information from all motion vectors simultaneously.…”
Section: A Databasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The test protocol used in the clinical trials specified that the arm be parallel to the ground, as the patient would usually be sitting or lying down. This position is recommended because the PPG devices are heavily impacted by motion artefacts, which are likely to have a significant influence on the quality of the measured data [82][83][84]. In Figure 18, the devices used in the clinical trials are shown, such as a gateway, an optical biosensor, a smartphone, and the developed wristwatch sensor platform are illustrated.…”
Section: System Implementation and Clinical Trialsmentioning
confidence: 99%